DEGRADASI LAHAN PADA BERBAGAI TANAMAN PERKEBUNAN DI KABUPATEN DHARMASRAYA SUMATERA BARAT - Syafrimen Yasin; Herviyanti Herviyanti; David David (Jurusan Tanah Fakultas Pertanian Universitas Andalas, 2005)
A reseach about determination land degradation on several plantation ecosystems in Dharmasraya Regency, West Sumatra. This research was aimed to study types of perennial crops (trees) which contributes to alleviate land degradation. The work was conducted in Sungai Rumbai Dystrict, Dharmasraya regency and in Soil Science Laboratory, Agriculture Faculty Andalas University. Soil samplings were taken at Ultisols having 0-8% slope (flate-undulating). Land use type being considered was original forest, oil palm, rubber, coffee, and cocoa plantation. Composite soil samples were taken for four replications on 1-20 cm depth. At each sampling site was accompanied by five drilling soils. Then, four undisturbed soil was also sampled at the same depth with disturbed soil samples for determining soil bulk density values. The data collected were analyzed statistically by using analyses of variance, and then continued by using Least Significant Difference (LSD) at 5% level. The result showed that rubber and cacao plantation contributed to better soil ecology value than oil palm and coffee land use. It could be proved from organic carbon (OC) and bulk density (BV) of the soils which were alsmost the same as those from forest land use. Key Words: Land degradation, plantation crops